Design and implementation of an all-digital timing recovery system for asynchronous communication - Valenciano-Rojas, José Jaime (2015)
This work addresses the design and implementation of a timing recovery unit for a communication system with parallel reception, 4-PAM modulation, raised cosine filtering and a nominal sampling frequency of 1,1 GHz. The design of the building blocks within the system, as well as simulation results and the physical implementation in FPGA are discussed.